PERAN KEPUASAN WISATAWAN SEBAGAI MEDIASI PENGARUH PENGALAMAN WISATAWAN TERHADAP MINAT BERKUNJUNG KEMBALI - Lalimu, Muhlis; Madjit, Rahmat; Yusuf, Yusuf; Usman, Usman (Journal Economics Technology And Entrepreneur, 2025)
This study aims to examine the mediating role of tourist satisfaction in the relationship between tourist experience and revisit intention at Ngurbloat Beach, Manyeuw District, Southeast Maluku Regency. Data were collected through a questionnaire distributed to 100 tourists and analyzed using the Partial Least Squares (PLS) method. The results show that tourist experience has a positive and significant impact on both tourist satisfaction and revisit intention. Additionally, tourist satisfaction also has a positive and significant effect on revisit intention. The findings confirm that tourist satisfaction acts as a partial mediator in the relationship between tourist experience and revisit intention. Therefore, improving the quality of the tourist experience significantly and directly influences tourists’ intention to revisit the destination.